Developing educational curricula in the Kingdom of Saudi Arabia and its impact on international tests’ results compared to the experiences of England, Finland, and Singapore - Almatroodi, Azizh Abdullah (Journal of Curriculum and Teaching Methodology, 2023)
This study aimed to identify the impact of curriculum development on the targeted learning outcomes within the educational system, as evaluated by international assessments. This is achieved by drawing from the experiences of three countries that have achieved advanced results in international assessments: England, Finland, and Singapore. The purpose is to assess the potential impact of curriculum development by evaluating international assessments of learners and providing curriculum planners, educators, and policymakers with valuable feedback, This study adopted a comparative descriptive approach through Geroge Beriday’s approach that adopted on description and explanation, interview, and comparison. Which is suitable for educational field issues and reform processes. Based on the experiences of the comparative countries, England, Singapore, and Finland, the study highlighted that curriculum development plays a crucial role in improving learners’ performance within the educational system and in international assessments that evaluate their performance at both national and global levels. Curriculum development can contribute to a deeper understanding of educational concepts and topics, enhancing learners’ comprehension and knowledge, and ultimately improving their ability to respond to test questions effectively. The researcher proposed several ways to enhance curriculum development in the Kingdom of Saudi Arabia, including enabling students to apply technology in real-world scenarios and promoting global culture, among other strategies.